The success rate of oral appliances based on multiple criteria according to obstructive sleep apnoea severity, BMI and age: A large multicentre study. (20th July 2020) - Okuno, Kentaro; Furuhashi, Akifumi; Nakamura, Shuhei; Suzuki, Hiroshi; Arisaka, Takehiro; Taga, Hitoshi; Tamura, Masataka; Katahira, Haruto; Furuhata, Minoru; Iida, Chisato
Abstract: Background: The efficacy of oral appliance (OA) varies greatly in patients with obstructive sleep apnoea (OSA). Objective(s): The purpose of this cross‐sectional study was to investigate the success rate of OA for OSA patients. Methods: This study was based on a cross‐sectional multicentre survey of OA therapy for the management of OSA called the JAMS (Japanese Cross‐sectional Multicenter Survey) Study performed at 10 medical institutions. A total of 442 patients fulfilled the selection criteria, which patients had worn OA, and undergone overnight polysomnography to assess both the pre‐treatment baseline and follow‐up for OA. Age, sex, BMI and apnoea‐hypopnea index (AHI) at the time of diagnosis and follow‐up for OA were extracted. Results: After OA treatment, the mean AHI decreased from 22.6 ± 13.8 to 10.0 ± 10.2/h, and the mean rate of decrease in the AHI was 52.5 ± 38.4%. Regarding the success rate to OA therapy, criterion 1 (AHI < 5/h), criterion 2 (AHI < 10/h), criterion 3 (AHI < 15/h) and criterion 4 (AHI reduction rate ≥ 50%) accounted for 33.5, 66.3, 80.5 and 63.3%, respectively. The success rate of OA treatment decreased according to the increase in OSA severity, obesity level (higher BMI) and older age. Conclusions: This study revealed the treatment success rate of OA on multiple criteria according to OSA severity, BMI and age. It may support for the clinician to make a decision on the OSA management.